An Analysis of Onomatopoeia in Peanut Comic By Charles M. Schulz - Muhammad Rifqi Firdaus; Mei Hardiah; Indah Damayanti (Journal of English Education and Teaching, 2021)
The aim of this research is to find out the type of onomatopoeia that used in the comic, the meaning of the onomatopoeic word, and the syllabic structure of the onomatopoeic word. The object of this research is a Peanut comic by Charles M. Schulz. The theory used in this research is based on Ullman’s theory. The result showed that there were two types of onomatopoeias found in the comic, the primary and secondary onomatopoeias. From 71 words, the dominant type found was the secondary onomatopoeia. It was also found that some forms of onomatopoeia have the same word with different meaning, depended on the subject and object that produces the sound. Some words come up more than once according to the storyline in the comic. The form of syllabic structure that the mostly used is Consonant-Consonant-Vocal-Consonant or CCVC, there were 20 out of a total 71 onomatopoeia that have the CCVC form.